Sequential multiple target detection using particle filters - Garcia Fernandez, Angel; Grajal, J. (2011)
We create and compare three sequential hypothesis tests for multiple target detection using particle filters. The algorithm with best performance assigns a variable number of particles to each hypothesis according to the posterior probabilities to optimise computational resources. Besides, the posterior probabilities of the hypotheses are calculated in a robust way regarding sample degeneracy. © 2011 IEEE.